¿Why public health is fair? - Rocha Buelvas, Anderson; Hidalgo Patiño, Carlos Alberto (Universidad y Salud, 2014)
This document is a reflection that seeks to promote the ethical-political discussion of justice in modernity. The implications of the public policies and the organization of health care systems are reviewed, especially when the current discussion of equity in health involves assessing inequalities from a sense of justice. Articles that addressed justice in public health from a purely ethical-political view were chosen. The search for information was obtained in several databases such as Medline, Proquest, Science Direct, Ovid, as well as on websites of national magazines and organizations.